Control of predatory aquatic insects (Ranatra dispar and Lithocerus insulanus) by using palm oil - OKONJI, V A; ASINI, E E (The Indian Journal of Animal Sciences, 2014)
The effects of palm oil in the eradication of predatory aquatic insects, viz. Ranatra dispar and Lithocerus insulanus were investigated. The experiment was carried out indoors with plastic buckets of 15 litres capacity. The oil was applied @ 0.5ml/ 10 litres of water. A total of 10 of each insect species was applied into each experimental unit and each treatment was replicated 4 times. The experiment was designed as a 2 (insect species) x 13 (hourly interval) factorial experiment in a completely randomised design. Data was collected and tested using table of analysis of variance (ANOVA) and graph. Palm oil was effective in achieving 100% mortality for both insect species but at different time intervals (P